Modelling, evaluating and implementing cost-effective services to reduce the impact of stroke - Charles DA Wolfe; Anthony G Rudd; Christopher McKevitt (NIHR Journals Library, 2014)
Background: Stroke is a leading cause of death and disability but there is little information on the longer-term needs of patients and those of different ethnic groups. Objectives: To estimate risk of stroke, longer-term needs and outcomes, risk of recurrence, trends and predictors of effective care, to model cost-effective configurations of care, to understand stakeholders' perspectives of services and to develop proposals to underpin policy. Design: Population-based stroke register, univariate and multivariate analyses, Markov and discrete event simulation, and qualitative methods for stakeholder perspectives of care and outcome. Setting: South London, UK, with modelling for estimates of cost-effectiveness. Participants: Inner-city population of 271,817 with first stroke in lifetime between 1995 and 2012. Outcome measures: Stroke incidence rates and trends, recurrence, survival, activities of daily living, anxiety, depression, quality of life, appropriateness and cost-effectiveness of care, and qualitative narratives of perspectives. Data sources: South London Stroke Register (SLSR), qualitative data, group discussions. Results: Stroke incidence has decreased since 1995, particularly in the white population, but with a higher stroke risk in black groups. There are variations in risk factors and types of stroke between ethnic groups and a large number of strokes occurred in people with untreated risk factors with no improvement in detection observed over time. A total of 30% of survivors have a poor range of outcomes up to 10 years after stroke with differences in outcomes by sociodemographic group. Depression affects over half of all stroke patients and the prevalence of cognitive impairment remains 22%. Survival has improved significantly, particularly in the older black groups, and the cumulative risk of recurrence at 10 years is 24.5%. The proportion of patients receiving effective acute stroke care has significantly improved, yet inequalities of provision remain. Using register data, the National Audit Office (NAO) compared the levels of stroke care in the UK in 2010 with previous provision levels and demonstrated that improvements have been cost-effective. The treatment of, and productivity loss arising from, stroke results in total societal costs of £8.9B a year and 5% of UK NHS costs. Stroke unit care followed by early supported discharge is a cost-effective strategy, with the main gain being years of life saved. Half of stroke survivors report unmet long-term needs. Needs change over time, but may not be stroke specific. Analysis of patient journeys suggests that provision of care is also influenced by structural, social and personal characteristics. Conclusions/recommendations: The SLSR has been a platform for a range of health services research activities of international relevance. The programme has produced data to inform policy and practice with estimates of need for stroke prevention and care services, identification of persistent sociodemographic inequalities in risk and care despite a reduction in stroke risk, quantification of the effectiveness and cost-effectiveness of care and development of models to simulate configurations of care. Stroke is a long-term condition with significant social impact and the data on need and economic modelling have been utilised by the Department of Health, the NAO and Healthcare for London to assess need and model cost-effective options for stroke care. Novel approaches are now required to ensure that such information is used effectively to improve population and patient outcomes. Funding: The National Institute for Health Research Programme Grants for Applied Research programme and the Department of Health via the National Institute for Health Research Biomedical Research Centre award to Guy's and St Thomas' NHS Foundation Trust in partnership with King's College London.